INVESTIGATION OF ANTIMICROBIAL, ANTIBIOFILM, ANTIOXIDANT POTENTIAL AND SEED MORPHOLOGY OF CAMELINA SATIVA L. CRANTZ - Ulgen, Hatice; Bulbul, Ali Savas; Ceylan, Keyser Betul (Parlar Scientific Publications (P S P), 2020)
Camelina sativa L. Crantz is one of the commonly known seven Camelina species in the Brassicaceae family and is the only species of economic importance in the genus Camelina. In this study, DMSO extracts of Camelina sativa L. seed oil were obtained. Antibacterial and antifungal activities of these extracts against twenty bacteria and one fungus, respectively, were investigated using the disc diffusion method. In addition, the antimicrobial activities of DMSO extracts were analyzed by methods of minimum inhibitory concentration (MIC) and minimum bactericidal/bacteriostatic concentration (MBC). Crystal violet binding assay was applied in order to evaluate the biofilm inhibition potential of extracts. DPPH (2,2-diphenyl-1-picrilhydrazil) method was applied to clarify their antioxidant activity. Finally, Camelina sativa L. seeds were examined under stereomicroscope and scanning electron microscopy (SEM) to evaluate the systematic importance of the seed microstructure. In conclusion, it has been found that Staphylococcus epidermidis is the most sensitive bacteria to seed oil extracts whose antimicrobial activity is determined. 40 mu l/ml concentration of seed oil had a higher antioxidant activity than other concentrations. Seed oil extracts of Camelina sativa L. showed the highest antibiofilm activity against Salmonella infantis and inhibited biofilm formation by 47.45% at a concentration of 80 mu l/ml.
Keywords: Antibiofilm Activity; Antimicrobial Activity; Antioxidant Activity; Camelina Sativa L.; Seed Morphology